2016
DOI: 10.18203/2349-3259.ijct20160996
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl as an adjuvant for brachial plexus block: a randomized comparative study

Abstract: Background: Adjuvants are known to enhance the effect of local anaesthetics (LA). Several adjuvants have been suggested to enhance the duration and analgesic effect of local anesthetic agents. We designed this randomized single blinded prospective study to compare the analgesic efficacy of Fentanyl used as an adjuvant to ropivacaine for supraclavicular brachial plexus block in patients undergoing orthopaedic surgeries of forearm. Methods: For this randomised prospective, single blinded study 66 ASA I and II pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…mentioned in their study that fentanyl used with ropivacaine prolonged the duration of sensory and motor blockade, probably by directly binding with opioid binding sites on the dorsal nerve roots aided with these axonal transports or by diffusing into surrounding tissues and subsequently into the epidural and subarachnoid spaces; it may also have been central opioid receptor mediated after systemic absorption of fentanyl. [ 2 ] Regarding, MBP changes;results showed statistically significance in our study for dexmedetomidine This came in agreement with Rashmi and Komala. [ 14 ] Regarding onset of sensory and motor anesthesia, results showed statistically significance in our study for dexmedetomidine as adjuvant which has earlier onset of anesthesia than fentanyl group and control group while fentanyl has earlier onset than control group which came in agreement with Bharti et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…mentioned in their study that fentanyl used with ropivacaine prolonged the duration of sensory and motor blockade, probably by directly binding with opioid binding sites on the dorsal nerve roots aided with these axonal transports or by diffusing into surrounding tissues and subsequently into the epidural and subarachnoid spaces; it may also have been central opioid receptor mediated after systemic absorption of fentanyl. [ 2 ] Regarding, MBP changes;results showed statistically significance in our study for dexmedetomidine This came in agreement with Rashmi and Komala. [ 14 ] Regarding onset of sensory and motor anesthesia, results showed statistically significance in our study for dexmedetomidine as adjuvant which has earlier onset of anesthesia than fentanyl group and control group while fentanyl has earlier onset than control group which came in agreement with Bharti et al .…”
Section: Discussionsupporting
confidence: 90%
“…mentioned in their study on fentanyl as adjuvant in brachial plexus nerve block that the mechanism of fentanyl in prolongation of analgesia may be due to the existence of peripheral functional opioid receptors, but this existence in peripheral tissue is still doubtful. [ 2 ] Furthermore, Rajkhowa et al . mentioned in their study that fentanyl used with ropivacaine prolonged the duration of sensory and motor blockade, probably by directly binding with opioid binding sites on the dorsal nerve roots aided with these axonal transports or by diffusing into surrounding tissues and subsequently into the epidural and subarachnoid spaces; it may also have been central opioid receptor mediated after systemic absorption of fentanyl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkalinisation of local anaesthetic agents in nerve block has been shown to improve onset, quality and duration of analgesia. 16,17,18,19 The same observation is concluded in a study by Tejwant Rajkhowa, Nilotpal Das, Samit Parua, et al, 8 on effect of fentanyl as an adjuvant for brachial plexus block, single blinded study 66 ASA I and II patients aged 18-65 years were included and were divided into 2 groups, group R (35) and RF (31). Supraclavicular brachial plexus block was performed in the group R using 0.5% ropivacaine 30 ml plus 1 ml NS (total 31 ml) and in group RF received 0.5% Compared to group R, group RF showed a significant greater duration of sensory and motor blockade ropivacaine plus 50 micrograms fentanyl in 1 ml NS (total 31 ml) in brachial plexus block.…”
Section: Discussionsupporting
confidence: 55%
“…15 Rajkhowa et al also demonstrated improved success rate and duration of analgesia with addition of 50µg of fentanyl to 0.5% ropivacaine in supraclavicular brachial plexus block. 16 In another study when 100µg of fentanyl added to axillary brachial plexus block, a doubling of postoperative analgesia was observed. 17 Prolongation of postoperative analgesia was reported in other studies also.…”
Section: Discussionmentioning
confidence: 95%